Integrating pneumonia prevention and treatment interventions with immunization services in resource-poor countries - Adam L Cohen; Terri B Hyde; Jennifer Verani; Margaret Watkins (The World Health Organization, 2012)
Pneumonia is a leading cause of morbidity and mortality worldwide. Effective vaccine and non-vaccine interventions to prevent and control pneumonia are urgently needed to reduce the global burden of the disease. This paper explores practical strategies and policies for integrating interventions to prevent and treat pneumonia with routine immunization services, and it investigates the challenges involved in such integration. The primary pneumonia prevention and treatment strategies that are implemented during routine childhood immunization visits are vaccination of children against the disease, caretaker education and referral of children to medical services when necessary.